PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris pada indeks LQ 45 yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014-2018) - Maptuha, Mamat; Hanifah, Imam Abu; Ismawati, Iis (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
This research is meat to analyze the effect of capital structure, liquidity and firm size on firm value with profitability as an intervening variable. The population in this study is the LQ 45 index companies listed on the Stock Exchange in 2014-2018 using annual financial report data taken by purposive sampling, so that 24 (twenty four) samples that meet the criteria are obtained. The sampling criteria chosen were 1) Companies that were consistently listed on the LQ 45 index in 2014-2018. 2) LQ 45 index companies that report financial reports for the end of December 31, complete with notes on financial statements (CALK) for the years 2014-2018. 3) Companies that use rupiah as their financial reporting currency. 4) Companies that report positive profits in their financial reporting. The analysis technique used is multiple linear regression analysis and path analysis with a significant level of 5%, the results of this study indicate that: 1) Capital structure (DER) has a significant negative effect on profitability. 2) Liquidity (CR) has a significant negative effect on profitability. 3) Firm size (SIZE) has a significant negative effect on profitability. 4) Capital structure (DER) has a significant positive effect on firm value (TOBIN'S Q). 5) Liquidity (CR) has no significant negative effect on firm value (TOBIN'S Q). 6) Firm size (SIZE) has no significant negative effect on firm value (TOBIN'S Q). 7) Profitability (ROA) has a significant positive effect on firm value (TOBIN'S Q). 8) Profitability (ROA) is able to mediate the effect of structure (CR) on firm value (TOBIN's Q). 9) Profitability (ROA) is not able to mediate the effect of liquidity (CR) on firm value (TOBIN's Q). 10) Profitability (ROA) is not able to mediate the effect of firm size (SIZE) on firm value (TOBIN's Q).